Four Questions on China in Africa. An Interview with Christopher Alden - (:unkn) unknown (My University, 2019)
Professor Alden is currently visiting scholar at CERI and has agreed to answer to some of our questions on the China/Africa relationship. Chris Alden has been working on this topic since 1990, when he moved to South Africa to do field work for his PhD on South African foreign policy. While teaching at Wits University in Johannesburg, he set up with a colleague the “East Asia Project” which started the first academic study of this topic based in the region. Interview by Miriam Perier, CERI.
Keywords: African Research